Microbial diversity and food safety in duck meat preservation: effects of nanoemulsion nutmeg seed extract with focus on proteobacteria and lactococcus - Supamri Supamri; Lilik Eka Radiati; Agus Susilo (CyTA - Journal of Food)
This study explores the innovative use of nanoemulsions from nutmeg seed extract for preserving duck breast meat, focusing on their impact on microbial diversity and functional pathways. Preservation was achieved through spray application using 15% microemulsion (MEp15) and 5% nanoemulsion (NEp5) formulations of nutmeg seed extract. Amplicon analysis of 16S rRNA revealed NEp5’s dual role in suppressing harmful Proteobacteria (e.g. Acinetobacter, 8.94 ± 3.99%) while enhancing beneficial Lactococcus (17.31 ± 8.35%). KEGG data highlighted NEp5’s ability to predict microbial functional pathways associated with cancer and metabolic disorders after 21 days of duck breast meat storage, outperforming MEp15 and control treatments. This study develops effective natural extract nanoemulsions as an eco-friendly preservation technology with significant potential to extend meat shelf life while ensuring safety and sustainability.